Dynamic contrast‐enhanced MRI of the prostate: An intraindividual assessment of the effect of temporal resolution on qualitative detection and quantitative analysis of histopathologically proven prostate cancer. Issue 5 (20th September 2016) - Ream, Justin M.; Doshi, Ankur M.; Dunst, Diane; Parikh, Nainesh; Kong, Max X.; Babb, James S.; Taneja, Samir S.; Rosenkrantz, Andrew B.
Abstract : Purpose: To assess the effects of temporal resolution (RT ) in dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) on qualitative tumor detection and quantitative pharmacokinetic parameters in prostate cancer. Materials and Methods: This retrospective Institutional Review Board (IRB)‐approved study included 58 men (64 ± 7 years). They underwent 3T prostate MRI showing dominant peripheral zone (PZ) tumors (24 with Gleason ≥ 4 + 3), prior to prostatectomy. Continuously acquired DCE utilizing GRASP (Golden‐angle RAdial Sparse Parallel) was retrospectively reconstructed at RT of 1.4 sec, 3.7 sec, 6.0 sec, 9.7 sec, and 14.9 sec. A reader placed volumes‐of‐interest on dominant tumors and benign PZ, generating quantitative pharmacokinetic parameters (k trans, ve ) at each RT . Two blinded readers assessed each RT for lesion presence, location, conspicuity, and reader confidence on a 5‐point scale. Data were assessed by mixed‐model analysis of variance (ANOVA), generalized estimating equation (GEE), and receiver operating characteristic (ROC) analysis. Results: RT did not affect sensitivity (R1all : 69.0%–72.4%, all P adj = 1.000; R1GS≥4 + 3 : 83.3–91.7%, all P adj = 1.000; R2all : 60.3–69.0%, all P adj = 1.000; R2GS≥4 + 3 : 58.3%–79.2%, all P adj = 1.000). R1 reported greater conspicuity of GS ≥ 4 + 3 tumors at RT of 1.4 sec vs. 14.9 sec (4.29 ± 1.23 vs. 3.46 ± 1.44; P adj = 0.029). No other tumor conspicuity pairwise comparison reached significance (R1all : 2.98–3.43, all P adj ≥ 0.205; R2all : 2.57–3.19, all P adj ≥ 0.059; R1GS≥4 + 3 : 3.46–4.29, all other P adj ≥ 0.156; R2GS≥4 + 3 : 2.92–3.71, all P adj ≥ 0.439). There was no effect of RT on reader confidence (R1all : 3.17–3.34, all P adj = 1.000; R2all : 2.83–3.19, all P adj ≥ 0.801; R1GS≥4 + 3 : 3.79–4.21, all P adj = 1.000; R2GS≥4 + 3 : 3.13–3.79, all P adj = 1.000). k trans and ve of tumor and benign tissue did not differ across RT (all adjusted P values [ P adj ] = 1.000). RT did not significantly affect area under the curve (AUC) of K trans or ve for differentiating tumor from benign (all P adj = 1.000). Conclusion: Current PI‐RADS recommendations for RT of 10 seconds may be sufficient, with further reduction to the stated PI‐RADS preference of RT ≤ 7 seconds offering no benefit in tumor detection or quantitative analysis. Level of Evidence : 3 J. MAGN. RESON. IMAGING 2017;45:1464–1475